Constructing a Study Buddy Using MERN (MongoDB, Express.js, React, Node.js) Stack Technologies - Chamalla Sravani; Pudi Kumar; Sanapala Priya; Sujith Kumar Yadav; Madina Jayanthi Rao; Urlam Devi Prasan (Engineering proceedings, 2024)
The “Study Buddy” project innovates by creating a dynamic web application that cultivates collaboration and support within the student community. This initiative harnesses the full potential of the MERN (MongoDB, Express.js, React, Node.js) stack to optimize student interactions, accelerate the learning process, and assist with a broad spectrum of academic and non-academic requirements. It revolutionizes how students engage, enabling them to share knowledge, pose queries, and offer assistance, ensuring robust security through authentication and authorization. Additionally, it empowers students to voice their concerns, propose groundbreaking ideas, and forge meaningful connections. This initiative fosters an inclusive and vibrant student environment, where information flows artlessly, challenges are met head-on, and students can thrive academically and beyond.